Preparation of pyridylamido hafnium complexes for coordinative chain transfer polymerization - Park, Kyung Lee; Baek, Jun Won; Moon, Seung Hyun; Bae, Sung Moon; Lee, Jong Chul; Lee, Junseong; Jeong, Myong Sun; Lee, Bun Yeoul (Polymers, 2020)
The pyridylamido hafnium complex (I) discovered at Dow is a flagship catalyst among postmetallocenes, which are used in the polyolefin industry for PO-chain growth from a chain transfer agent, dialkylzinc. In the present work, with the aim to block a possible deactivation process in prototype compound I, the corresponding derivatives were prepared. A series of pyridylamido Hf complexes were prepared by replacing the 2,6-diisopropylphenylamido part in I with various 2,6-R2C6H3N-moieties (R = cycloheptyl, cyclohexyl, cyclopentyl, 3-pentyl, ethyl, or Ph) or by replacing 2-iPrC6H4C(H)- in I with the simple PhC(H)-moiety. The isopropyl substituent in the 2-iPrC6H4C(H)-moiety influences not only the geometry of the structures (revealed by X-ray crystallography), but also catalytic performance. In the complexes bearing the 2-iPrC6H4C(H)-moiety, the chelation framework forms a plane; however, this framework is distorted in the complexes containing the PhC(H)-moiety. The ability to incorporate α-olefin decreased upon replacing 2-iPrC6H4C(H)-with the PhC(H)-moiety. The complexes carrying the 2,6-di(cycloheptyl)phenylamido or 2,6-di(cyclohexyl)phenylamido moiety (replacing the 2,6-diisopropylphenylamido part in I) showed somewhat higher activity with greater longevity than did prototype catalyst I.
Keywords: Alpha-olefins; Catalytic performance; Chain growth; Chain transfer agents; Chain transfer polymerization; Compound I; Deactivation process; Hafnium complexes; Coordinative chain transfer polymerization; Dialkylzinc; Polyolefin; Post-metallocene; Pyridylamido hafnium complex